Colorful Box Media as a Cognitive Intervention: Enhancing Three-Seriation Classification Skills in Children Aged 4–5 Years - Wafiq Azizah; Yudhi Purwa Nugraha (South Sulawesi Education Development (SSED), 2026)
Purpose: This study examines the effectiveness of colorful box media as a concrete manipulative intervention to enhance the three-seriation object classification skills of children aged 4–5 years in early childhood education settings. Methodology: A Classroom Action Research (CAR) design following Kurt Lewin's cyclical model was employed across two cycles, each comprising planning, implementation, observation, and reflection phases. Sixteen children (7 boys, 9 girls) from Group A of TK PGRI Kabere participated. Data were collected via structured observational checklists aligned with national early childhood development standards (Permendikbud No. 137/2014), covering three classification dimensions: colour, shape, and size. Mastery criteria followed an 80% class completion threshold. Results: In Cycle I, 44% of children (n = 7/16) achieved mastery, with persistent difficulties in shape and size classification attributed to ambiguous basket coding and insufficient pre-activity scaffolding. Following targeted modifications in Cycle II, including shape-congruent basket design, competitive game elements, and explicit pre-play orientation, the mastery rate reached 100% (n = 16/16), surpassing the required minimum criterion. Conclusions: Colorful box media constitutes an effective, low-cost concrete manipulative for promoting logical classification in young children, provided that material design is developmentally aligned, multi-dimensional in scope, and embedded in structured play-based pedagogical routines. Findings contribute to the evidence base for hands-on media design in early childhood cognitive education.